Anaemia in Pregnancy, Severity and Outcome in Lumbini Province, Nepal - Sharma, Deepanjali; Lamsal, Manoj; Subedi, Jigyasa; KC, Tara; Banu, Hasina; Manandhar , Bekha Laxmi (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Anemia is common nutritional deﬁciency disorder in pregnant women. It is important cause of morbidity and mortality among pregnant women. We evaluated pregnant women presenting to UCMS-TH with hemoglobin level less than 9 gm/dl with reference to maternal and fetal outcome. MATERIAL AND METHODS Total of 255 women presenting with moderate to severe anemia at our hospital were evaluated. Demographic proﬁle of patients, maternal outcomes and fetal outcomes were evaluated. RESULTS Most of patients were from rural area (78%) of which majority (69.8%) were unbooked. Severe anemia was present in 16.5% cases. Maternal complications included preterm labor (23.1%), post partum hemorrhage (19.2%), wound infection (8.6%), ante partum hemorrhage (5.5%), intensive care unit admission (4.3%) and mortality (0.4%). Fetal outcomes included neonatal intensive care unit admission (29.8%), intrauterine growth restriction (9%) and neonatal death (7.5%). CONCLUSION Severity of anemia associated with signiﬁcant increase in PPH, preterm delivery, ICU admission and heart failure.